Online academic examination system (OAESYS) A web-based examination system - Quinones, Alvin Jed M. (2005)
The project developed an automated system that can facilitate web-based examinations. The components of the system, consisting of the Administrator client, the Instructor client, and the Examinee website, function to provide an environment where examinations can be prepared with ease. Answers submitted by the students can be graded automatically by the system so that the test scores can be retrieved immediately after the examination. The system also supports the sharing of examinations between instructors leading to faster and more efficient preparation of new examinations. Support for a rich set of examination types is also provided, thereby providing more freedom and diversity to the examination design. Moreover, by using the system, instructors will be able to conduct online examinations in any location with network or internet access given that the presence of a human supervisor is available during examination proper to ensure the examinees follow the examination guidelines correctly and to prevent students from cheating
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2005